PERTUMBUHAN DAN PERKEMBANGAN TUNAS Typhonium SECARA IN VITRO - Hoesen, Djadja Siti Hazar (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Study on shoots growth and development of Typhonium flagelliforme (Lodd.) Blume and T. trilobatum (L.) Schott were carried out by in vitro technique.These species produce tubers are used for cancer medication; also the whole parts of plants has been reported potential for traditional medicine. Chemicals isolated from from crude extract of whole plants of T.flagelliforme are methyl esters of hexedecanoic acid, octadecanoic acid, 9- octadecanoic acid and 9,12- octadecadienoic acid.The chemical contents inhibited/decreased the proliferation of human leukaemia cell lines in test.For medical and cosmetics industrial usage of the plants requires supply materials continously of which in turn necessitate its cultivation and planting. The planting materials can be produced efficiently by micro propagation or in vitro technique. The objective of the study was to evaluate the culture respond to the plant growth regulator (PGR) treatments effect. The experiment was designed with completely randomized designed (CRD).The study was indicated that proliferation of shoot were optimum in the growth medium was supplemented with N6-Benzyladenine (BA) 1mg/l and NAA 0,5 mg/l. Acclimatization stage and planted to the soil were successful, almost whole (90-95 %) plants were survive.